(untitled) (Revista Venezolana de Salud Pública, 2018)
Salmonella spp., is a Gram negative bacillus widely distributed at World which is a major public health problem with major economic and health implications. Salmonella species are the major cause of acute gastroenteritis in various countries. The present work corresponded to a prospective cross-sectional descriptive study, for which the prevalence of Salmonella spp., was determined, In 80 children aged 2 to 6 years in kindergartens of the Marruecos section of the resort Rafael Uribe Uribe (Bogota) in the period comprised between November 2010 and February 2011. ELISA method was used to establish the diagnosis of microorganism prevalence of 18,8%. According to the estimates of relative risk, socio-demographic characteristics such as gender are associated with the likelihood that the disease is more prevalent in males exposed to the Salmonella organism.